Kajian Teoretis tentang Teori Experiential Integration dalam Pembelajaran IPA Terpadu untuk Pemahaman Konseptual: Penelitian - Radetyo, Iqbal; Kuncahyono, Kuncahyono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop Experiential Integration Theory (EIT) as a new theoretical framework that explains the relationship between empirical experience and the formation of conceptual understanding in integrated science learning. This research is motivated by the gap between the application of experiential learning and the lack of a theoretical basis explaining how concrete experiences support the integration of concepts across disciplines. The study uses a conceptual analysis and theoretical synthesis approach by examining the theory of experience (Kolb, 1984), science integration theory (Fogarty, 1991; Czerniak, 2007), and relevant research from 2018–2025. The study process includes three stages: literature identification, thematic analysis to find epistemological relationships between theories, and the preparation of a theoretical synthesis that links the empirical and reflective-conceptual dimensions. The results of the study produce three main propositions: 1. Authentic experience triggers cross-concept integration, 2. Conceptual integration strengthens scientific reflection, 3. The reflection-integration cycle forms deep conceptual cohesion.